2006
DOI: 10.1016/j.otohns.2006.04.008
|View full text |Cite
|
Sign up to set email alerts
|

Systematic facial nerve monitoring in middle ear and mastoid surgeries: “Surgical dehiscence” and “electrical dehiscence”

Abstract: We recommend an electrical stimulation of 0.7 mA for the first screening and 0.4 mA for the second exploration in order to define the facial nerve using intraoperative NIM-2 monitoring in middle ear and mastoid surgeries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 18 publications
1
7
0
2
Order By: Relevance
“…We can argue that the 2 dehiscences found in Group 2 could be related to the technical limitation of the radiologic study or spontaneous dehiscence of the FC described in many articles (20Y23). This is consistent with the findings of Choung et al (24); they recommended the value of 0.7 mA for the first screening of ''electrical dehiscence,'' and they concluded that this parameter is safer than surgical dehiscence. Silverstein et al (25) also found that the value of 1 mA stimulation corresponded approximately at 1 mm of the remaining bone over the FN.…”
Section: Discussionsupporting
confidence: 90%
“…We can argue that the 2 dehiscences found in Group 2 could be related to the technical limitation of the radiologic study or spontaneous dehiscence of the FC described in many articles (20Y23). This is consistent with the findings of Choung et al (24); they recommended the value of 0.7 mA for the first screening of ''electrical dehiscence,'' and they concluded that this parameter is safer than surgical dehiscence. Silverstein et al (25) also found that the value of 1 mA stimulation corresponded approximately at 1 mm of the remaining bone over the FN.…”
Section: Discussionsupporting
confidence: 90%
“…However, dehiscence at the vestibular surface of the facial canal is usually out of the surgeon's point of view and may be open to an accidental injury. Choung et al have demonstrated that surgical dehiscence of the facial canal presented in 43% of cases while 73% of those responded to electrical stimulation which indicated an increased vulnerability to trauma and termed this condition as “electrical dehiscence” [21]. Routine monitorization of the facial nerve during surgery of chronic otitis media has been found to be effective and necessary [16, 21].…”
Section: Discussionmentioning
confidence: 99%
“…More recently, Choung et al also evaluated surgical dehiscence versus electrical dehiscence in 100 patients, prospectively 4. In 43% of cases, surgical dehiscence was noted.…”
Section: Literature Reviewmentioning
confidence: 99%